The complex origins of mouth polymorphism in the Labeobarbus (Cypriniformes: Cyprinidae) of the Inkisi River basin (Lower Congo, DRC, Africa): insights from an integrative approach. Issue 2 (10th September 2018) - Vreven, Emmanuel J W M N; Musschoot, Tobias; Decru, Eva; Wamuini Lunkayilakio, Soleil; Obiero, Kevin; Cerwenka, Alexander F; Schliewen, Ulrich K
Abstract: A morphological case study, including 25 meristics and 31 measurements of 37 Labeobarbus specimens from the Inkisi basin, Lower Congo, is presented. Two groups of specimens express either Labeobarbus -like (rubberlip) or Varicorhinus -like (chiselmouth) mouth phenotypes and a third group is morphologically intermediate. Rubberlip and chiselmouth specimens differ significantly from each other in some meristics and morphometrics, and all three phenotypes of this Inkisi complex form a strongly supported monophylum based on mitochondrial ( COI ) and nuclear (AFLP) DNA phylogenetic inferences. Tree-based analyses designed to differentiate between polymorphism, incipient speciation and hybridization scenarios, in combination with multivariate PCA of AFLP multilocus genotypes, revealed substantial, non-random genomic variation, which correlated strongly with the three major mouth phenotype groups and favours a scenario of secondary hybridization between primarily distinct parental lineages. Consequently, the two distinct mouth phenotypes are described taxonomically as species taxa and the various morphological intermediates are characterized as hybrid phenotypes. This study suggests that a new interpretation of the alpha-level taxonomy of the hexaploid Torini is necessary. These proposed changes are highlighted and discussed for African Torini. A typology of Labeobarbus mouth phenotypes was developed, which will be useful for future studies.